Herpes simplex virus thymidine kinase/ganciclovir system in multicellular tumor spheroids - Finocchiaro, L.M.E. (2004)
We have developed multicellular spheroids (MCS) established from LM05e and LM3 spontaneous Balb/c-murine mammary adenocarcinoma and B16 C57-murine melanoma derived cell lines as an in vitro model to study the efficacy of the herpes simplex virus thymidine kinase/ganciclovir (HSVtk/GCV) suicide system. We demonstrated for the first time that HSVtk-expressing cells assembled as MCS manifested a GCV resistance phenotype compared to the same cells grown as sparse monolayers. HSVtk-expressing LM05e, LM3 and B16 spheroids were 16-, three- and nine-fold less sensitive to GCV than their respective monolayers, even though they could express transgenes 10-, eight- and five-fold more efficiently. Mixed populations of HSVtk- and their respective βgal-expressing cells displayed a cell-type specific bystander effect that was higher in monolayers than in MCS. However, HSVtk-expressing cells in two- or three-dimensional cultures were always significantly more sensitive to GCV than the βgal-expressing counterparts, supporting the feasibility of this suicide approach in vivo. We present evidence showing that HSVtk-expressing tumor cells, when transferred from monolayers to MCS, displayed: (i) lower GCV cytotoxic activity and bystander effect; (ii) higher and efficient expression of genes transferred as lipoplexes; (iii) lower cell proliferation rates; and (iv) changes in intracellular Bax/Bcl-xL rheostat of mitochondria-mediated apoptosis.